The 'Cancer Home-Life Intervention': A randomised controlled trial evaluating the efficacy of an occupational therapy–based intervention in people with advanced cancer. (April 2018) - Pilegaard, Marc Sampedro; la Cour, Karen; Gregersen Oestergaard, Lisa; Johnsen, Anna Thit; Lindahl-Jacobsen, Line; Højris, Inger; Brandt, Åse
Background: People with advanced cancer face difficulties with their everyday activities at home that may reduce their health-related quality of life. To address these difficulties, we developed the 'Cancer Home-Life Intervention'. Aim: To evaluate the efficacy of the 'Cancer Home Life-Intervention' compared with usual care with regard to patients' performance of, and participation in, everyday activities, and their health-related quality of life. Design and intervention: A randomised controlled trial (ClinicalTrials.gov NCT02356627). The 'Cancer Home-Life Intervention' is a brief, tailored, occupational therapy–based and adaptive programme for people with advanced cancer targeting the performance of their prioritised everyday activities. Setting/participants: Home-living adults diagnosed with advanced cancer experiencing functional limitations were recruited from two Danish hospitals. They were assessed at baseline, and at 6 and 12 weeks of follow-up. The primary outcome was activities of daily living motor ability. Secondary outcomes were activities of daily living process ability, difficulty performing prioritised everyday activities, participation restrictions and health-related quality of life. Results: A total of 242 participants were randomised either to the intervention group ( n  = 121) or the control group ( n  = 121). No effect was found on the primary outcome (between-group mean change: −0.04 logits (95% confidence interval: −0.23 to 0.15); p =  0.69). Nor was any effect on the secondary outcomes observed. Conclusion: In most cases, the 'Cancer Home-Life Intervention' was delivered through only one home visit and one follow-up telephone contact, which not was effective in maintaining or improving participants' everyday activities and health-related quality of life. Future research should pay even more attention to intervention development and feasibility testing.